Postponing Pregnancy for Economic Reasons: An Islamic Juridical-Empirical Study in Air Genting Village, Asahan - Putri, Fatia Aisyah; Irwan (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to examine the perspectives of scholars in Asahan regarding the postponement of pregnancy due to economic factors and its implications for married couples in Air Genting Village. While Islam encourages procreation as part of the sunnah, couples often consider financial stability, health, and psychological readiness before deciding to have children. This research employs a qualitative field study with a juridical-empirical approach. Data were gathered through observations and in-depth interviews with married couples who have chosen to delay pregnancy, as well as discussions with local scholars to understand the Islamic legal perspective on this issue. The collected data were analyzed descriptively, with triangulation applied to ensure the validity of findings. The findings reveal that economic concerns, particularly the ability to provide for children’s basic needs such as food, education, and healthcare, are the primary reasons for delaying pregnancy. However, scholars from the Indonesian Ulema Council (MUI) in Asahan assert that postponing pregnancy for financial reasons is not permissible in Islam, as each child’s sustenance is believed to be guaranteed by Allah. Nonetheless, delaying pregnancy is considered acceptable if done for health-related reasons or to ensure maternal and child well-being through birth spacing. This study contributes to the discourse on Islamic family planning by providing empirical evidence on how economic factors influence reproductive decisions within the framework of Islamic law, specifically in the local context of Asahan. The study highlights the need for educational programs on pregnancy planning that align with Islamic teachings while addressing economic realities. Additionally, policymakers should consider strategies to improve the economic welfare of young couples, enabling them to make informed reproductive choices without financial distress.